M – phủ tối tiểu và các hệ Sperner với vấn đề tìm kiếm khóa của quan hệ cơ sở dữ liệu - Que, Pham The (Journal of Computer Science and Cybernetics, 2018)
In this paper, we investigate the properties of M-minimal covers when a finite set H and the Sperner system on H are given. Specially, we establish the necessary and sufficient condition for which two sperner system are the set of all representative sets for the set of keys we can determine the set of keys for the relation scheme. The set of keys for the relation scheme is just the set of all representative sets for the set of all  representative sets for the set of keys.